0130 Central and Peripheral Markers of Oxidative Stress and Sleep in Mood Disorder: A Pilot MR Spectroscopy Study. (25th May 2022) - Busler, Jessica; Grant, Leilah; Liao, Vicky; Lin, Alexander; Rahman, Shadab; Mahon, Pamela
Abstract: Introduction: Sleep disturbance is both a symptom of and a risk factor for mood disorders. Oxidative stress may impact the relationship between sleep disturbance and mood. However, the relationships between sleep and in vivo measurements of oxidative stress in the brain have not been examined in humans. Therefore, we tested the relationship between patient-reported sleep disturbance with peripheral and central concentrations of glutathione (GSH), the primary antioxidant in the brain. Methods: Participants (2 women and 7 men) were individuals with (n=2) and without mood disorder (n=7), ages 35-61 years. MR spectroscopy at 7 Tesla (TE=20ms, TM=10ms, TR=3000ms) was used to measure cortical GSH levels in the brain in the anterior cingulate cortex (ACC), ventromedial prefrontal cortex (VMPFC), and dorsolateral prefrontal cortex (DLPFC). Peripheral GSH was assayed from a fasted morning blood draw. Sleep disturbance and related impairment was assessed via the PROMIS Sleep Disturbance (PROMIS-SD) and Sleep-Related Impairment (PROMIS-SRI) questionnaires. Pearson correlations were assessed between peripheral and central GSH levels with PROMIS-SD and PROMIS-SRI T-scores. Results: We observed significant negative correlations between DLPFC GSH with sleep disturbance (r=-0.744, p=0.022) and sleep-related impairment (r=-0.753, p=0.019). We did not detect correlations between sleep-related endpoints and peripheral GSH levels or GSH levels in the ACC or VMPFC. Conclusion: These preliminary results suggest that more sleep disturbance and related impairment may be associated with lower levels of cortical GSH and implicate a role for sleep disturbance to impact oxidative stress in a region associated with rapid eye movement sleep and modulation of affective states. Support (If Any): This work was supported by grants from the National Institutes of Health R01MH110979 (PBM) and T32MH017119 (JB).